GYY4137 attenuates LPS-induced acute lung injury via heme oxygenase-1 modulation. (February 2019) - Jiang, Lei; Jiang, Qing; Yang, Songlin; Huang, Shicong; Han, Xiaoli; Duan, Jun; Pan, Shangha; Zhao, Mingyan; Guo, Shuliang
Abstract: GYY4137, a slow-releasing hydrogen sulfide (H2 S) donor, has been reported to exert anti-inflammatory activity and protect against sepsis. Heme oxygenase-1 (HO-1) is an important anti-inflammatory heat shock protein and plays a similar effect on sepsis. This study investigated the role of GYY4137 in acute lung injury (ALI) via HO-1 regulation. Lung injury was assessed in mice challenged with intratracheal lipopolysaccharide (LPS) and the mechanism of anti-inflammatory effects of GYY4137 was investigated in mice and RAW264.7 cells. GYY4137 reduced the LPS-mediated pulmonary injury and neutrophil infiltration, and inhibited the LPS-induced production of proinflammatory cytokines, inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) expression. Moreover, GYY4137 suppressed the LPS-evoked NF-κB activation in RAW264.7 cells. GYY4137, not time-expired GYY4137 significantly induced HO-1 expression compared with the LPS group. The beneficial effects of GYY4137 above were reversed by the HO-1 inhibitor tin protoporphyrin (SnPP). These results suggest an anti-inflammatory effect and a therapeutic role of GYY4137 in LPS-induced ALI via HO-1 regulation.